2014
DOI: 10.1179/1743284713y.0000000317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reheating temperature and time on microstructure and tensile properties of thixoforged AZ63 magnesium alloy

Abstract: The effects of two main processing parameters such as reheating temperature and reheating time on microstructure and tensile properties of thixoforged AZ63 magnesium alloy have been investigated. The results indicate that these two parameters all have large effects on the microstructure and tensile properties. However, in contrast, the effects of the reheating temperature on liquid fraction and liquid composition of semisolid ingot, and thus the subsequent solidification behaviour and plastic deformation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Besides, they found that the ignition temperatures increase with increasing melt viscosities. Chen et al [30,31] investigated the impact factors on microstructure and tensile properties of thixoforged AZ63 magnesium alloys. The results suggested that the mould temperature affected the solidification behavior, plastic deformation and recrystallization during thixoforging by changing solidification rate.…”
mentioning
confidence: 99%
“…Besides, they found that the ignition temperatures increase with increasing melt viscosities. Chen et al [30,31] investigated the impact factors on microstructure and tensile properties of thixoforged AZ63 magnesium alloys. The results suggested that the mould temperature affected the solidification behavior, plastic deformation and recrystallization during thixoforging by changing solidification rate.…”
mentioning
confidence: 99%
“…Moreover, both the size and number of the cavities increased as the temperature elevated. It is known that SSS were the weak points of the thixoformed materials because shrinkage porosities and pores always existed in these structures [40]. Meanwhile, its compatible deformation ability was poor due to the existence of hard and fragile eutectics and SiC p .…”
Section: Effect Of Temperature On Tensile Fracture Behaviormentioning
confidence: 99%
“…Therefore, the debonding of SiC p as well as void nucleation and growth were the main fracture mechanisms in the composite at high temperature, and increasing the testing temperature (less than 250 • C) induced relatively improved ductility of the composite, but the elongation decreased when the temperature exceeded 250 • C due to the extensive cavity formation. pores always existed in these structures [40]. Meanwhile, its compatible deformation ability was poor due to the existence of hard and fragile eutectics and SiCp.…”
Section: Effect Of Temperature On Tensile Fracture Behaviormentioning
confidence: 99%
“…Grain growth by coalescence by grain boundary migration is dominant for short times after the liquid is formed, and Ostwald ripening is dominant for longer times [22]. This is a common phenomenon in thixoforged materials [23][24][25]. The Mg2Si particles and the liquid might be engulfed by the merged primary α-Mg grains, so Mg2Si particles or the eutectic β phase would distribute inside the primary α-Mg grains in the thixoforged specimens.…”
Section: Microstructural Analysismentioning
confidence: 99%